PSEUDOANEURYSM OF THE LEFT VENTRICULAR APEX AFTER TRANSFEMORAL TRANSCATHETER AORTIC VALVE IMPLANTATION PROCEDURE – CASE REPORT - Robert Kasza,; Lidia Ziętek, (International Journal of Innovative Technologies in Social Science, 2026)
Aortic stenosis represents one of the most prevalent degenerative valvular defects in the aging population. The advent of Transcatheter Aortic Valve Implantation (TAVI) has facilitated the effective treatment of high-risk patients who were previously disqualified from surgery. While this minimally invasive method significantly reduces the risk of perioperative complications compared to traditional surgery, it does not entirely eliminate them. The occurrence of life-threatening mechanical complications following TAVI is uncommon but requires immediate recognition. This study aims to present a rare case of an iatrogenic left ventricular pseudoaneurysm following a transfemoral procedure. This report details the case of a 73-year-old female patient with severe aortic stenosis and multiple comorbidities who underwent elective TAVI via transfemoral access. During the procedure, a stiff guidewire was positioned in the left ventricle. Although the implantation was technically successful, routine diagnostic imaging on the first postoperative day revealed an abnormality. Based on the patient's clinical condition, transthoracic echocardiography (TTE), and a subsequent contrast-enhanced Computed Tomography (CT) scan, a pseudoaneurysm of the left ventricular apex with active bleeding into the pericardial sac was confirmed. The patient required urgent conversion to classical cardiac surgery. The left ventricular perforation was successfully repaired via median sternotomy, which resulted in the patient's recovery, albeit with a prolonged hospitalization. Bleeding complications remain one of the most common causes of surgical reoperation following TAVI. Such events have been demonstrated to significantly impact the risk of mortality and extend the overall duration of hospitalization. Formed apical pseudoaneurysms represent a particularly rare complication. in the literature, such cases are predominantly described in the context of transapical access, which necessitates traversing the heart wall. However, this case highlights that iatrogenic perforation of the ventricle by the guidewire can also occur during transfemoral access. Routine postoperative imaging is crucial for the early detection and successful management of this life-threatening condition.